Asymptotic Expansions of Jacobi Polynomials for Large Values of β and of Their Zeros - Gil, A.; Segura, J.; Temme, N.M. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
Asymptotic approximations of Jacobi polynomials are given for large values of the β-parameter and of their zeros. The expansions are given in terms of Laguerre polynomials and of their zeros. The levels of accuracy of the approximations are verified by numerical examples.